Geopolitical risks in international business – managing strategic resource dependence : A semiconductor industry perspective - Lundén, Onni (My University, 2025)
In an increasingly interconnected global economy, control over strategic resources such as semiconductors has become a critical issue for governments, as they are essential in reinforcing national security and technological innovation. The COVID-19 pandemic and rising geopolitical tensions between major powers, particularly the US and China, exposed significant vulnerabilities in the semiconductor supply chain, highlighting how disruptions from external shocks to that industry can affect the wider business environment. This leads to the central topic of the study: How can multinational corporations manage strategic resource dependency in a volatile geopolitical environment. This study examines the connections between geopolitical risk and resource dependency from the perspective of the semiconductor industry, focusing on the analysis of how firms navigate in a business environment where inputs are concentrated in politically sensitive regions, and where government influence restricts decision-making. The study uses a qualitative approach, supported by three connecting theoretical frameworks: resource dependence theory, strategic resource management theory, and techno-nationalism. The investigation is based on secondary data, consisting of journal articles, industry reports, policy documents and media coverage discussing the semiconductor industry. The collected data was analysed with a thematic methodology to identify key themes in the sources, based on a process of tagging, categorising, and refining the data to discover the main issues the industry is faced with. To complement this broad analysis, Intel Corporation was selected as a case example to analyse the findings from the practical perspective of a major company in the industry. The findings suggest that the primary geopolitical risks to the semiconductor industry are focused on the uncertainty with regards to trade restrictions and export controls, and the concentration of production to East Asia. Governments have started to put more emphasis on securing their semiconductor supply chains, with the US and EU enacting CHIPS Act-initiatives to reshore production and improve technological sovereignty. Intel has aligned with these objectives, taking advantage of the governmental support to restructure supply chains and geographically diversify production. The findings conclude that firms operating in geopolitically exposed industries must manage external dependencies by aligning with government industrial policies, while simultaneously developing internal capabilities to maintain a level of strategic autonomy. These insights contribute to both the theoretical discussion of resource dependence, and the practical discussion of geopolitical risk management in international business. The study can be seen as a snapshot of the current developments in the semiconductor industry, providing context for future research of the industry

Yhä verkottuneemmassa globaalissa taloudessa strategisten resurssien, kuten puolijohteiden, hallinnasta on tullut valtioille keskeinen aihe, sillä ne ovat olennaisia resursseja kansallisen turvallisuuden ja teknologisen innovaation vahvistamisessa. COVID-19-pandemia ja suurvaltojen, erityisesti Yhdysvaltojen ja Kiinan, väliset kiristyneet geopoliittiset jännitteet paljastivat merkittäviä haavoittuvuuksia puolijohteiden toimitusketjuissa, tuoden esiin miten toimialan ulkoisista häiriöistä johtuvat katkokset voivat vaikuttaa laajempaan liiketoimintaympäristöön. Tutkimuksen keskeinen tavoite on analysoida, miten monikansalliset yritykset voivat hallita strategisia resurssiriippuvuuksiaan epävakaassa geopoliittisessa toimintaympäristössä. Tämä tutkimus tarkastelee geopoliittisten riskien ja resurssiriippuvuuden yhteyttä puolijohdeteollisuuden näkökulmasta, keskittyen analysoimaan miten yritykset navigoivat toimintaympäristössä, jossa tuotantopanokset ovat keskittyneet poliittisesti herkille alueille ja jossa valtioiden vaikutusvalta rajoittaa yritysten päätöksentekoa. Tutkimuksessa käytetään laadullista lähestymistapaa, jota tukevat kolme toisiinsa linkittyvää teoreettista viitekehystä: resurssiriippuvuusteoria, strategisen resurssienhallinnan teoria ja teknonationalismi. Tutkimus perustuu toissijaiseen aineistoon, joka koostuu tieteellisistä artikkeleista, toimialaraporteista, poliittisista asiakirjoista ja median raportoinnista puolijohdeteollisuudesta. Kerätty aineisto analysoitiin temaattisella menetelmällä, jonka avulla tunnistettiin lähteiden yhdistävät teemat. Analyysi perustui aineiston koodaukseen, luokitteluun ja jalostamiseen, joiden kautta hahmottuivat toimialan keskeisimmät haasteet. Tämän laaja-alaisen tarkastelun tueksi Intel Corporation valittiin tapausesimerkiksi, jotta havaintoja voitiin tutkia myös käytännön näkökulmasta suuren toimialayrityksen kautta. Tutkimuksen tulokset osoittavat, että puolijohdeteollisuuden keskeiset geopoliittiset riskit liittyvät epävarmuuteen kaupan rajoituksista ja vientivalvonnasta, sekä tuotannon keskittymiseen Itä-Aasiaan. Hallitukset ovat alkaneet kiinnittää enemmän huomiota puolijohteiden toimitusketjujen turvaamiseen; Yhdysvallat ja Euroopan unioni ovat toteuttaneet CHIPS Act -aloitteita tuotannon palauttamiseksi kotimaahan ja teknologisen suvereniteetin vahvistamiseksi. Intel on linjannut strategiansa näiden tavoitteiden mukaisesti, hyödyntäen valtiollista tukea toimitusketjujen uudelleenjärjestelyssä ja tuotannon maantieteellisessä hajauttamisessa. Tulosten perusteella geopoliittisesti herkille toimialoille sijoittuvien yritysten tulee hallita ulkoisia riippuvuuksiaan asettumalla linjaan valtion teollisuuspoliittisten tavoitteiden kanssa, mutta kehittäen samalla sisäisiä kompetenssejaan strategisen autonomian säilyttämiseksi. Havainnot edistävät teoreettista keskustelua alan resurssiriippuvuudesta, ja käytännön ymmärrystä kansainvälisen liiketoiminnan geopoliittisesta riskienhallinnasta. Tutkimus toimii myös ajankohtaisena kuvauksena puolijohdeteollisuuden nykykehityksestä, tarjoten lähtökohtia alan tulevalle tutkimukselle.
Keywords: geopolitics, risk management, resource dependence, techno-nationalism, supply chain resilience, semiconductor industry, international business strategy, geopolitiikka, riskienhallinta, resurssiriippuvuus, teknonationalismi, toimitusketjujen resilienssi, puolijohdeteollisuus, kansainvälinen liiketoimintastrategia